Bibliography: economic Aspects of Terrorism - Tinnes, Judith (Perspectives on terrorism, 2021)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on economic aspects of terrorism (such as eco-terrorism, economic grievances and unemployment as root causes of terrorism, the economic impact of terrorist attacks, or financial costs of CT-measures). Literature on terrorist financing has been excluded as it will be covered separately. The bibliography focuses on recent publications (up to May 2021) and should not be considered as exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.